Mr. Docker is off his rocker! - Gutman, Dan (Gutman, Dan. My weird school, 2006)
Mr. Docker, a new science teacher, is a crazy inventor who blows things up, uses potatoes for power, and has A.J. and his friends wondering whether science is for nerds or is the coolest subject ever.